Learning to Cherish in Five Poems by Audre Lorde - Iis Wahyuli; Kurnia Ningsih (English Language and Literature, 2020)
This article entitled Learning to Cherish focuses on analyze the five poems by Audre Lorde which are Who Said It Was Simple, For Each Of You, A Woman Speaks, A Litany For Survival, and Movement Song. The problem in this analysis how far the five poems by Audre Lorde expose the issue of learning to cherish of the Black Women. The aim of this analysis is to find out how far the five poems by Audre Lorde expose the issue of learning to cherish in the Black women. This analysis is involved poetic elements that are imagery, repetition, speaker, and tone to reveal the issue. The analysis is related to the concept of Feminism by Bell Hook (1984) and Naomi Wolf (2002). The result of this analysis shows the Black women have good attitude and behavior to care deeply for their identity.